1991
DOI: 10.1038/jcbfm.1991.88
|View full text |Cite
|
Sign up to set email alerts
|

NADH Fluorescence and Regional Energy Metabolites during Focal Ischemia and Reperfusion of Rat Brain

Abstract: Summary: Transient focal ischemia was produced in rat brain using simultaneous, reversible occlusion of the mid dle cerebral artery (MCA) and both carotid arteries. NADH tissue fluorescence and regional levels of ATP and lactate were measured after occlusion for 1 or 2.5 h and after reperfusion for 1 or 24 h following a 2.5-h insult. Occlusion for 1 or 2.5 h caused a marked but microhet erogenous increase in NADH fluorescence, which was restricted to the MCA territory of the ipsilateral cortex. In this ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…Recordings made in intact brains as well as in brain slices following either transient ischemic or hypoxic episodes revealed a decrease of NADH fluorescence and cytochrome a,a 3 reflectance significantly below control levels, which has been interpreted as hyperoxidation of intra-mitochondrial oxidative enzymes Duckrow et al, 1981;Feng et al, 1998;Paschen et al, 1985;Perez-Pinzon et al, 1998a, 1997a, 1998bPulsinelli et al, 1982;Rosenthal et al, 1995Rosenthal et al, , 1997Siesjo, 1981;Tanaka et al, 1986;Welsh et al, 1991;Welsh et al, 1982). The alternative explanation of a depletion of the electron carrier pool has been rejected by other authors .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recordings made in intact brains as well as in brain slices following either transient ischemic or hypoxic episodes revealed a decrease of NADH fluorescence and cytochrome a,a 3 reflectance significantly below control levels, which has been interpreted as hyperoxidation of intra-mitochondrial oxidative enzymes Duckrow et al, 1981;Feng et al, 1998;Paschen et al, 1985;Perez-Pinzon et al, 1998a, 1997a, 1998bPulsinelli et al, 1982;Rosenthal et al, 1995Rosenthal et al, , 1997Siesjo, 1981;Tanaka et al, 1986;Welsh et al, 1991;Welsh et al, 1982). The alternative explanation of a depletion of the electron carrier pool has been rejected by other authors .…”
Section: Introductionmentioning
confidence: 87%
“…Previous studies have shown hyperoxidation to be inversely related to adenosine 5′-triphosphate (ATP) recovery but directly correlated with histopathology (Welsh et al, 1991). Since the aged brain has shown increased vulnerability to hypoxic/ischemic damage Chih, 1995, Roberts andChih, 1998;Roberts et al, 1990), it is conceivable that injury to the aged brain will be exacerbated by the combined effects of changes in calcium buffering, prolonged hsd and resulting NADH hyperoxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed both in vivo and in vitro suggest that reperfusion after ischemia or reoxygenation after hypoxia leads to NAD(P)H hyperoxidation [8][9][10]. Studies describing NAD(P)H autofluorescence changes throughout ischemia/reperfusion in brain tissue or slices do not reveal the respective contribution of neurons and glial cells to the global emission.…”
Section: Introductionmentioning
confidence: 97%
“…NADH fluorescence has also been measured in vivo under a number of altered physiological conditions including spreading depression and ischemia (Anderson et al, 1999;Tomlinson et al, 1993;Welsh et al, 1991). In more recent reports, NADH fluorescence was imaged from the cortex following middle cerebral artery occlusion using charge coupled device (CCD) cameras (Strong et al, 1996;Strong et al, 2000).…”
Section: Nadh and Flavoprotein Autofluorescencementioning
confidence: 99%